2013
DOI: 10.1002/hec.2934
|View full text |Cite
|
Sign up to set email alerts
|

From Social Capital to Health – And Back

Abstract: We assess the causal relationship between health and social capital, measured by generalized trust, both at the individual and the community level. The paper contributes to the literature in two ways: it tackles the problems of endogeneity and reverse causation between social capital and health by estimating a simultaneous equation model, and it explicitly accounts for mis-reporting in self-reported trust. The inter-relationship is tested using data from the first four waves of the European Social Survey for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 97 publications
(140 reference statements)
6
69
0
3
Order By: Relevance
“…Other studies have used corruption, population density, regional citizenship rates and religious fractionalization as IVs. Some of these studies corroborated some of the observed associations between social capital and health (Kim et al, 2011; Rocco & Suhrcke, 2012). To our knowledge, no studies have used these methods to assess whether social capital is associated with both objective and subjective health in a low- or middle-income country.…”
Section: Introductionsupporting
confidence: 67%
“…Other studies have used corruption, population density, regional citizenship rates and religious fractionalization as IVs. Some of these studies corroborated some of the observed associations between social capital and health (Kim et al, 2011; Rocco & Suhrcke, 2012). To our knowledge, no studies have used these methods to assess whether social capital is associated with both objective and subjective health in a low- or middle-income country.…”
Section: Introductionsupporting
confidence: 67%
“…European countries found support for a positive relationship between self-perceived health 14 and social capital and that it acts in both directions (Rocco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The positive relationships between social capital and human health are well documented [25,26,27,28,29]. Social capital and “catch” activities were seen as strongly tied i.e.…”
Section: Resultsmentioning
confidence: 99%